Neferura : the pharaoh's daughter - Evans, Malayna (Sourcebooks Landmark, 2024)
"For readers of The Wolf Den and Kaikeyi comes the thrilling tale of the forgotten daughter of a legendary Egyptian pharaoh and the path she must take to escape her own dangerous fate. There are many paths to power. They all come with a price. Neferura, princess and high priestess of Kemet, knows her duty is to her people. When your mother is the great Pharaoh, it is hard to forget. But Neferura's unique position at court comes with high stakes for her country, especially when she's forced to serve her vile half-brother, a man determined to stop Neferura's potential rise. Peace, it seems, never lasts for women who wield power in the open. Especially when they cross a vengeful man. When Neferura overhears Thutmose's plot to end her mother's rule, she knows he must be stopped, no matter the cost. The discovery of a mysterious tattooed wisewoman and her shadowy network of spies offers an uneasy alliance. But the wisewoman wields more power than Neferura knew possible -- power with the potential to rival her own. Neferura must decide where her loyalties lie and how much she's willing to sacrifice to protect the people she loves before everything crumbles at the hands of a tyrant"--